EVALUATION OF ANTIBACTERIAL ACTIVITY OF GREEN-SYNTHESIZED SILVER NANOPARTICLES AGAINST PATHOGENIC BACTERIA (Journal of Medical & Health Sciences Review, 2025)
There is an urgent need to find alternative therapeutic agents because pathogenic bacteria are becoming more resistant to antibiotics. The broad-spectrum antimicrobial qualities of silver nanoparticles (AgNPs) have gained interest. Plant extract-mediated reduction was utilized in this study to produce silver nanoparticles, giving a sustainable, economical, and environmentally friendly substitute for conventional chemical processes. To verify their formation, surface chemistry, and morphology, the synthesized AgNPs were examined using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and UV-Vis spectroscopy. Using the agar well diffusion method, the antibacterial activity of the green-synthesised AgNPs was assessed against a number of pathogenic bacterial strains, such as Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli. The antimicrobial efficacy has been assessed by measuring the zones of inhibition. Significant antibacterial activity has been demonstrated by the results, and larger inhibition zones were seen for Gram-negative bacteria than for Gram-positive strains, indicating differences in cell wall susceptibility. Furthermore, it was discovered that the activity was dose-dependent, meaning that higher AgNP concentrations had greater antibacterial effects. The findings indicate that green-synthesised silver nanoparticles have powerful antibacterial qualities and show potential as a substitute for traditional antibiotics, particularly when addressing bacterial infections that are resistant to drugs. This study emphasizes the significance of combining nanotechnology and green chemistry for sustainable biomedical solutions and supports the use of biosynthesized nanoparticles in the fabrication of novel antimicrobial agents.